PENGARUH TOTAL ASSETS TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PT ASTRA INTERNATIONAL Tbk PERIODE 2010-2022 - Agung Hartoyo, Septian; Nurcahayati, Siti (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Total Assets Turnover and Debt to Equity Ratio on Return on Assets at PT Astra International Tbk for the period 2010-2022. The research method uses quantitative descriptive. The research population is financial statements, with samples including balance sheets and profit and loss, selected through purposive sampling method. The data analysis used is the classical assumption test, multiple linear regression analysis, t-test hypothesis testing, F-test and the Coefficient of Determination (R2) test. The t test results show that TATO has a sig value of 0.000 < 0.05 and a tcount value of 7.193 > t table 2.228, this means that partially TATO has a significant effect on ROA. DER has a sig value of 0.097 > 0.05 and a tcount value of -1.831 < t table 2.228, this means that partially DER has no significant effect on ROA. Meanwhile, the results of the F test research show that the sig value is 0.000 < 0.05 and Fcount 48.848 > Ftable 4.10, this means that TATO and DER simultaneously affect ROA. The test results of the Coefficient of Determination (R2) show an R-square of 0.907, this means that simultaneously the effect of TATO and DER on ROA has a contribution of 90.7% while the remaining 9.3% is influenced by other factors not examined in this study.